Food texture experiences across age groups in 4‐ to 36‐month‐old children in the United States. Issue 1 (8th December 2021) - Surette, Victoria A.; Smith‐Simpson, Sarah; Fries, Lisa R.; Ross, Carolyn F.
Abstract: The question of what to feed becomes a new challenge as an infant reaches the transition to complementary foods. Limited information is available that provides a texture progression map for complementary food introduction. Thus, the objective of this study was to determine the relationship between age and food texture experiences (FTE) in young children aged 4–36 months in the United States. A parent‐reported survey was fielded with 328 children categorized into five age groups (AGs): 4–8 months (AG1), 9–12 months (AG2), 13–18 months (AG3), 19–24 months (AG4), and 25–36 months (AG5). The present study analyzed four questions focused on FTE, with statistical analyses including probit and logit models, and analysis of variance. Results showed that all 16 food textures were tried at least once (>50%) by AG3. The question answered by participants, "How well does your child manage a specific texture, " showed that significant differences existed among AGs for the management of 10 food textures (including chewy, hard, soft ), whereas teething alone had no effect. The most refused textures by the children were AG1— crispy (27%), AG2— leafy (23%), AG3— leafy (40%), AG4— tough meat (52%), and AG5— leafy (51%). With increasing AG, the refusal probability of nine food textures, including chewy, leafy, and rubbery, also increased ( p < .05). The refusal probability of cold food temperatures decreased with increasing age ( p < .05). This study observed FTE in children across AGs and provides useful information to parents and practitioners as they introduce food textures into children's diets. Abstract : The objective of this study was to determine the relationship between age and food texture experiences in young children using a parent‐reported survey of 328 children (between 4 and 36 months). Results showed differences in food texture management across age groups as well as differences in food texture refusals. From these data, this study proposes a texture progression map for the complementary food introduction period.